Analisis Peraturan Menteri Dalam Negeri Nomor 20 Tahun 2018 Tentang Pedoman Pengelolaan Keuangan Desa (Studi Kasus pada Desa Kacinambun, Kecamatan Tigapanah, Kabupaten Karo) - Angelina Yunita Munte; Puspita Geatri Br Perangin-Angin; Nuwun Priyono (Jurnal Riset Akuntansi, 2023)
This article aims to gain an understanding of how village financial management is implemented based on Permendagri Number 20 of 2018 concerning Guidelines for Village Financial Management, as well as to evaluate the extent to which these changes have an impact on implementation in the field through a case study in Kacinambun village, Tigapanag District, Karo Regency. The research approach used in this article is a descriptive qualitative method, with data sources obtained from primary data by interviewing village financial management officials and secondary data through literature or books concerned with the research title. The findings from this study indicate that village financial management is carried out with reference to Permendagri Number 20 of 2018, but there are problems that arise due to the slow performance of heads of affairs in carrying out their duties. This delay has had an impact on the disbursement of funds and hindered the progress of village development, as well as causing delays in reporting budget realization.